The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0474
|View full text |Cite
|
Sign up to set email alerts
|

A new method to determine air shower propagation direction based on radio signal patterns

Abstract: The propagation direction is one of the key parameters of an air shower. In this study we introduce a new and unique approach to determine propagation direction of an air shower based on filtered peak radio amplitudes which can shape radio signal patterns. For this purpose, a series of simulations were performed with CORSIKA and CoREAS software. Simulated air showers initiate from Proton and Iron primary particles with 10 17 eV energy and have different zenith angles from vertical to 60°. Time based results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…These two type of figures are almost identical four all kind of cosmic rays regardless of their initial energy and type of primary particle as we discussed in [3]. These patterns also contain some valuable information about the arrival direction of a cosmic ray [15].…”
Section: Ground Footprints At Srasupporting
confidence: 58%
“…These two type of figures are almost identical four all kind of cosmic rays regardless of their initial energy and type of primary particle as we discussed in [3]. These patterns also contain some valuable information about the arrival direction of a cosmic ray [15].…”
Section: Ground Footprints At Srasupporting
confidence: 58%
“…Earlier analyses have shown that it is possible to drive some of the key parameters of an air shower from radio measurement only [12]]. It is possible to even determine an air shower propagation direction based on radio signal patterns [13]. However there is always a question which needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the progress made in this field, it is now possible to determine some of the most important characteristics of a cosmic ray like energy, direction and type of primary particle from radio measurements only [10], [11]. Previous studies have also shown the possibility of determining an air shower propagation direction based on the lateral distribution analyses [12]. The other important parameter is a place where the extensive air shower axis hits the ground, the shower core.…”
Section: Introductionmentioning
confidence: 99%